2013
DOI: 10.1055/s-0033-1360163
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydramnios: Causes, Diagnosis and Therapy

Abstract: Introduction !Polyhydramnios is the term used to describe an excess accumulation of amniotic fluid. This clinical condition is associated with a high risk of poor pregnancy outcomes [1][2][3]. The reported prevalence of polyhydramnios ranges from 0.2 to 1.6 % of all pregnancies [4][5][6][7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 87 publications
2
95
1
3
Order By: Relevance
“…It may be due to some preventive measures taken in our medical centers, because various protocols have been used in different studies and as a result some variable consequences were reported. Hamza et al (19) found a direct relationship between gestational diabetes and polyhydramnios in women with PPROM; with the gestational diabetes was associated with the risk of polyhydramnios leading to PPROM. In our study some significant statistical differences were found in the average hospital stay period before childbirth, the average interval between admission and childbirth, the average latent phase length of the vaginal childbirth and the average interval between rupture of membrane and childbirth in control group in contrast to women with gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…It may be due to some preventive measures taken in our medical centers, because various protocols have been used in different studies and as a result some variable consequences were reported. Hamza et al (19) found a direct relationship between gestational diabetes and polyhydramnios in women with PPROM; with the gestational diabetes was associated with the risk of polyhydramnios leading to PPROM. In our study some significant statistical differences were found in the average hospital stay period before childbirth, the average interval between admission and childbirth, the average latent phase length of the vaginal childbirth and the average interval between rupture of membrane and childbirth in control group in contrast to women with gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 2% of all pregnancies have an excess amount of fluid meeting the criteria for polyhydramnios[1,2]. It is reported in the literature that approximately sixty percent of polyhydramnios is idiopathic; twenty percent of polyhydramnios can be attributed to poorly controlled or undiagnosed diabetes and the remainder of cases of polyhydramnios are associated with fetal anomalies[2-4].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes is one of the common causes of polyhydramnios, but the pathogenesis has not been elucidated yet [28,29]. Possible explanation is increased osmotic diuresis which subsequently leads to polyuria in GDM [29].…”
Section: Implications Of Gestational Diabetesmentioning
confidence: 99%